Unit apartemen dengan supply energi surya suatu analisis ekonomi dan manajemen dalam Design Engineering (D/E) - Nurhamdoko Boni (University of Merdeka Malang, 2003)
The typical flow of thought (input, process, output, restriction, and feedback) which is generally accepted for each different subsystem, can still be relied upon as a tool in engineering design subsystems. Improvements with the addition of the feasibility study and procurement subsystems, simplify the phasing of the development process of a project. Without going through the discussion of the procurement subsystem, the development budget will swell. The quality of materials, components, equipment, and machines will not be commensurate with the price paid. The procurement stage allows ordering goods, tools, and machines without waiting for the processes from other stages to be completed. Applying the combined CADD technology, component database with software creation (menu system) that bridges it in the design process, will result in an amazing process speed, thus speeding up the idea into a reality. Application of solar cell technology, which requires quite complex calculations and is trial and error, becomes easy, fast, and accurate because this work is completely taken over by the computer